2022
DOI: 10.1097/hcr.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Informed Virtual World-Based Cardiac Rehabilitation Program as an Extension of Center-Based Cardiac Rehabilitation

Abstract: This study assessed the feasibility and acceptability of a novel virtual world-based CR (VWCR) program, Destination Rehab, as an extension of a conventional center-based CR program. The VWCR program is a feasible, highly acceptable, and innovative platform to potentially influence health behaviors and CV risk and may increase accessibility to disadvantaged populations with higher CV disease burdens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…Aligning with the performance objectives, nine interventional methods were identified to perform CR at home, including guided practice, goal setting, planning coping responses, self-monitoring of behaviors, discussion, information about other’s approval, stimulating communication, mobilizing social support, and interpersonal contact. The findings are supported by previous studies where interventional strategies of peer support and reflection discussion were used in a community-informed virtual world-based CR program ( 47 ). A systematic review ( 48 ) showed that methods of social support and goal setting were frequently adopted in the home-based CR program.…”
Section: Discussionsupporting
confidence: 87%
“…Aligning with the performance objectives, nine interventional methods were identified to perform CR at home, including guided practice, goal setting, planning coping responses, self-monitoring of behaviors, discussion, information about other’s approval, stimulating communication, mobilizing social support, and interpersonal contact. The findings are supported by previous studies where interventional strategies of peer support and reflection discussion were used in a community-informed virtual world-based CR program ( 47 ). A systematic review ( 48 ) showed that methods of social support and goal setting were frequently adopted in the home-based CR program.…”
Section: Discussionsupporting
confidence: 87%
“…A total of N = 22 articles were included in this review. 1839 The studies varied in research designs, including 11 randomized controlled trials, 1820,23,26,27,3033,35 five pilot studies, 21,24,25,28,36 two observational studies, 29,34 one case study, 22 one qualitative study, 37 one mixed-method study, 38 and one cross-sectional study. 39 The studies had been conducted in different locations: 11 of them in Europe, 1820,22,28,31,3336,39 six in Asia, 23,24,29,30,32,37 three in Australia, 2527 and two in...…”
Section: Resultsmentioning
confidence: 99%
“…Patients participating in the group-based cardiac telerehabilitation were required to have their own, relevant technological equipment with Internet access (computer, telephone, and mobile connection). 1839 A variety of other devices and applications were also used in the included studies (Supplemental Material Table 3). Out of the 22 studies, a chat feature was primarily utilized as a means of delivering the intervention in 15 studies, 21,22,2427,2932,34,35,3739 telemonitoring, 18,20,24,2830,3237,39 and a virtual platform 2125,28,3032,34,35,37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Going forward, changes in the way we deliver CR services need to be rooted in science. Critically, as we consider alternatives to the traditional CR model, 13,14 we need to consider the patient perspective. More research is needed regarding the effectiveness of alternative models of CR in rural, remote, diverse and, otherwise, underserved populations.…”
mentioning
confidence: 99%